Redefining Gender in Early Childhood: Inclusive Practices for Pre-K Education - Alviar Rueda, Elvia Jimena; Rojas Rodríguez, Daniel Hernando (Ciencia Latina Revista Científica Multidisciplinar, 2025)
This study focuses on integrating gender inclusivity into Kindergarten 2 English as a Foreign Language (EFL) classrooms in Bogotá, Colombia. It explores how societal norms influence young children’s attitudes, behaviors, and identities, highlighting how education can challenge stereotypes and promote fairness. Using Action Research, two cycles of activities were implemented to help students reflect on and question traditional gender roles, fostering a more inclusive environment. The findings show that including gender awareness in language lessons boosts empathy, critical thinking, and acceptance of diversity, transforming the classroom into a space where all identities are valued. This work emphasizes the importance of teachers as role models for inclusion and social justice. Ultimately, it shows that teaching English can go beyond language skills to address important social issues, helping students develop broader, more equitable perspectives from a young age.